(untitled) (Eurasian Scientific Herald, 2022)
The importance of sports tourism and national sports in our country. This article discusses the efforts in the field of sport tourism, increasing the number of tourist bases as a result of increasing the number of mountain resorts, the development of the capacity of the National Olympic Committee, the Ministry of Tourism.